Chondrogenic Differentiation of Human Bone Marrow-Derived Mesenchymal Stem Cells in Self-Gelling Alginate Discs Reveals Novel Chondrogenic Signature Gene Clusters - Herlofsen, Sarah Roxana (Mary Ann Liebert, Inc., 2011)
We have used a disc-shaped self-gelling alginate hydrogel as a scaffold for in vitro chondrogenic differentiation of human bone marrow-derived mesenchymal stem cells. The comparison of monolayer cells and alginate embedded cells with or without differentiation medium allowed us to perform a detailed kinetic study of the expression of a range of genes and proteins known to be involved in chondrogenesis, using real-time polymerase chain reaction, fluorescence immunohistochemistry, and glycosaminoglycan measurement in the supernatant. mRNA encoding type II collagen (COL2), COL10, aggrecan, and SOX5, 6, and 9 were greatly elevated already at day 7, whereas COL1 and versican mRNA were gradually reduced. COL2 and aggrecan were dispersed throughout the extracellular matrix at day 21, whereas COL10 distribution was mainly intra/pericellular. COL1 seemed to be produced by only some of the cells. SOX proteins were predominantly localized in the nuclei. Then, using microarray analysis, we identified a signature cluster of extracellular matrix and transcription factor genes upregulated during chondrogenesis similar to COL2A1, and clusters of genes involved in immune responses, blood vessel development, and cell adhesion downregulated similar to the chemokine CXCL12. Analysis of the signature chondrogenic clusters, including novel potential marker genes identified here, may provide a better understanding of how the stem cell fate could be directed to produce perfect hyaline cartilage implants.